Analysis of the Formation of Government Regulations as Separation of Powers in Indonesia - Fajri Halim (Jurnal Indonesia Sosial Teknologi, 2024)
Indonesia is a constitutional state where government administration is based on statutory regulations hierarchically proposed by the law as mandated by the 1945 Constitution. The authority to implement laws is translated into government and other laws and regulations. The order of laws and regulations is used as a "rule" when a government activity is to be carried out. However, in practice, there are still mechanisms for forming PPs that are inconsistent with the orders of the law. This study aims to determine the basis and mechanism for forming PP as an executive authority and the legal implications of not issuing PP by the executive. The type of research is normative juridical with a literature study approach. The analysis shows that the process of forming laws can be studied from two perspectives, namely normative juridical and sociological perspectives. The material content of laws in Indonesia is complex to determine from the power-sharing system. However, it can be determined by looking at the system for forming statutory regulations, where it has been stated that the formation of statutory regulations must be based on hierarchical law. Suppose the executive does not issue a PP as mandated by the law. In that case, it will result in not achieving the ideals of the general norms contained in the law, and harmonisation of law implementation will not be realised. Even though it is a country based on law, no government administration in Indonesia is not based on statutory regulations as its legal basis